Where the Spirit Leads Me: The Autobiographical Holy Foremothers of Contemporary African American Women's Writing - Douglass-Chin, Richard J. (My University, 1998)
The autobiographies of the nineteenth-century black women evangelists, along with the petition of their strongly African eighteenth-century precursor Belinda, have never been examined collectively as a genre changing considerably throughout the nineteenth-century, and developing in a chiasmic return throughout the twentieth-century to give rise to contemporary African American women's literary forms. Through close readings of primary texts, I examine the ways in which the evangelists employ discourses produced by socio-economic determinants such as race, gender and class to create a complex black female narrative economy, with its own unique figurations and forms. These figurations and forms--for example the cult of the "unnatural" woman, the quest for community, the trope of trial, or the valorisation of the sermonic mode--develop and change over time. This changing black female spiritual narrative economy is indicative of an important line in the ongoing traditions of black women's writing which has only now begun to be reclaimed and validated. In their texts, evangelist autobiographers such as Rebecca Jackson, Sojourner Truth or Julia Foote maintained African traditions (for example, orality), and African American ways of being and telling (such as the preacheriy, or the performance of the blues) which were signified upon in the work of Zora Neale Hurston, and· are still of utmost importance to many African American women writers today.
Keywords: African American Women; Writing